Effect of ground contact pressure and soil settlement period on paddy transplanter sinkage - Garg, I K; Mittal, V K; Sharma, V K (Journal of Agricultural Engineering, 2000)
A study was carried out on to find out the desirable sinkage of a particular machine at which it would work efficiently under different soil conditions. The tests were conducted at 4 levels of ground contact pressures and 4 levels of soil settlement period in case of silt-clay loam (soil S1) and 3 levels of sandy loam (soil S2). In soil S1, maximum sinkage of 4.30 cm was observed at the highest ground contact pressure of 24.44 g/cm² and at the lowest soil settlement period of 23 hours. The minimum sinkage of 0.48 cm was at the lowest ground contact pressure of 6.11 g/cm² and at the highest settlement period of 72 hours. In soil S2, maximum sinkage of 5.13 cm was at the highest ground contact pressure of 24.44 g/cm² and at the lowest soil settlement period of 2 hours. The minimum sinkage of 0.15 cm was at the lowest ground contact pressure of 6.11 g/cm² and at the highest settlement period 24 hours. In general, sinkage increased with the increase in ground contact pressure and decrease in soil settlement period after puddle for both the soils.